Pemahaman Sejarah Sebagai Penguatan Cinta Tanah Air dan Relevansinya dengan Pendidikan Agama Islam - Wahid Tuftazani Rizqi (Berkala Ilmiah Pendidikan, 2023)
Indonesia, which is known as a country with the largest Muslim majority in the world, has a history steeped in elements of tolerance. However, at present, many incidents have actually harmed the value of tolerance, for example, the issue of radicalism and the issue of terrorism. There needs to be a re-understanding of the history of the founding of this nation so that future generations can understand that the nation's founding fathers already had a sense of love for the motherland and an attitude of respect for differences. This research is qualitative and relies on library research. The approach used is a historical approach, with the data collection method using the documentation method and the data analysis using content analysis. The results of the study show that there are values of love for the motherland in the form of defending the country, participating in efforts to defend the country, and respecting human rights. This value also has relevance to Islamic Religious Education, especially in the teaching materials in SMA Class XII.